2020
DOI: 10.1039/d0nh00242a
|View full text |Cite
|
Sign up to set email alerts
|

MBenes: emerging 2D materials as efficient electrocatalysts for the nitrogen reduction reaction

Abstract: MBenes hold many merits for electrocatalysis of the nitrogen reduction reaction, including outstanding stability in aqueous environments, excellent electrical conductivity, an inhibited hydrogen evolution reaction, and highly active boron and metal surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 60 publications
6
89
0
Order By: Relevance
“…Although some MBene compounds have not yet been synthesized experimentally, theoretical predictions have verified that some MBenes can be electrochemical catalysts by theoretical studies. [ 16 ] Therefore, a large number of theoretical studies have reported that Pt(100) is suitable for the reaction of NO reduction to NH 3 , which is more difficult than N 2 and N 2 O formation. [ 17 ] However, NORR studies are mainly focused on metal‐based catalysts and single atom catalysts, but these catalysts usually face poor stability and require a high working potential during the NORR process.…”
Section: Introductionmentioning
confidence: 99%
“…Although some MBene compounds have not yet been synthesized experimentally, theoretical predictions have verified that some MBenes can be electrochemical catalysts by theoretical studies. [ 16 ] Therefore, a large number of theoretical studies have reported that Pt(100) is suitable for the reaction of NO reduction to NH 3 , which is more difficult than N 2 and N 2 O formation. [ 17 ] However, NORR studies are mainly focused on metal‐based catalysts and single atom catalysts, but these catalysts usually face poor stability and require a high working potential during the NORR process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] In particular, the abundant metal atoms distributed in basal plane can potentially provide partially occupied d orbitals to enhance the adsorption of small molecules, such as N 2 and other reaction intermediates, in the NRR process. [ 23 ] We note that, though the activity of several MBenes have been recently evaluated, [ 24 ] a large composition space of MBenes awaits explorations. [ 25 ] To achieve a rational design of optimal configuration toward NRR, it is important to identify the characteristics of the active sites, and to find out the suitable descriptors to evaluate their catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the limiting potential (η) of NRR on Fe 3 @C 2 N is as low as −0.57 V, lower than the η values on the Ru (0001) step surface [40] and Fe 2 @C 2 N [24] (0.98 eV and 1.23 eV, respectively). Typically, the potential limiting step on most metal surfaces (such as Re, Ru, Rh and Fe) or two-dimensional MBenes is either the first hydrogenation (forming *NNH) or the last protonation (*NH 3 formation or NH 3 desorption) [9,41]. However, on Fe 3 @C 2 N, the free energy change of *N 2 → *NNH is only 0.28 eV.…”
Section: N 2 Reaction On Fe 3 @C 2 Nmentioning
confidence: 99%